Needs Assessment in Health Research Projects: A New Approach to Project Management in Iran - Niloofar Peykari; Parviz Owlia; Hossein Malekafzali; Mostafa Ghanei; Abdolreza Babamahmoodi; Shirin Djalalinia (Tehran University of Medical Sciences, 2013)
Background: The science and technology health plan has defined the outline of health research to the national vision of Iran by 2025. The aim of this study was to focus on the process of needs assessment of health research projects also health research priority setting in Iran.Methods: The project management life cycle has four phases: Initiation, Planning, Execution and Closure. Based on abovementioned points we conducted the study.Results: Focusing on the needs assessment led to systematic implementation of needs assessment of health project in all of the medical sciences universities. Parallel with this achieved strategies health research priority setting was followed through specific process from empowerment to implementation.Conclusion: We should adopt with more systematic progressive methods of health project managements for both our national convenience as well as our international health research programs.